Numerical simulation and performance evaluation of filter-equipped solar chimney power plants. (5th January 2023) - Yoo, Seungwoo; Oh, Sahuck; Hachicha, Ahmed Amine
Abstract: A solar-assisted large-scale cleaning system (SALSCS) is a solar thermal system that utilizes the concept of a solar chimney power plant (SCPP) to improve outdoor air quality. In an SALSCS, air purification is facilitated by passing the buoyancy-induced airflow through an air filter installed in the system. In the current study, a new solar chimney system called a filter-equipped SCPP (FSCPP), which is a hybrid of SCPP and SALSCS, is proposed and investigated to identify the possibility of generating electrical power and purifying outdoor air simultaneously. A three-dimensional numerical model is developed to study the heat transfer and fluid flow inside the solar chimney. The simulation method is implemented and validated with experimental data from the literature. The simulation results reveal that the pressure drop is higher across the filter than at the turbine in the FSCPP, indicating a higher energy consumption at the filter. Numerical simulations are also carried out to compare the performance of the SCPP, SALSCS and FSCPP. The results show that the FSCPP has the lowest volume flow rate and the highest temperature rise. The electrical power generated by the FSCPP is only about 20 ∼ 40% of the SCPP's power generation, but its air purification capabilities approximate those of the SALSCS, with only a 2 to 4% reduction. The influence of the system's dimensions on overall system performance is also analyzed. The FSCPP shows an enhancement in primary capabilities (i.e., power generation and air purification) with an increase in the width and height of the solar chimney system of up to 200 m. Highlights: A filter-equipped solar chimney power plant (FSCPP) system is proposed. Numerical simulations are conducted to evaluate the performance of FSCPPs. The electrical power generation of FSCPP decreased by 20 to 40% compared to SCPP's capability. The air purification capability of FSCPP is almost similar (about 96 to 98%) to that of SALSCS.